Genetic polymorphism of cytochrome P450 2C9 in a Caucasian and a black African population - Scordo, Maria Gabriella (Blackwell Science Inc, 2001)
AIMS: CYP2C9 is a major enzyme in human drug metabolism and the polymorphism observed in the corresponding gene may affect the therapeutic outcome during treatment with several drugs. The distribution of variant CYP2C9 alleles was therefore investigated in an Italian and an Ethiopian population. METHODS: Allele-specific PCR analysis was carried out in order to determine the frequencies of the two most common variant alleles, CYP2C9*2 and CYP2C9*3 in genomic DNA isolated from 157 Italians and 150 Ethiopians. RESULTS: The frequencies of CYP2C9*1 (80%), CYP2C9*2 (11%) and CYP2C9*3 (9%) found in the Italian population were similar to other Caucasian groups. However in the Ethiopian population CYP2C9*1, CYP2C9*2 and CYP2C9*3 were present at a frequency of 94, 4 and 2% respectively. The 95% confidence intervals in CYP2C9*1, CYP2C9*2 and CYP2C9*3 between Italians and Ethiopians were 0.098, 0.176, 0.040, 0.098 and 0.040, 0.098, respectively. CONCLUSIONS: Our results indicate that the Ethiopian population has a unique relative distribution of the CYP2C9 alleles, which is not similar to any other ethnic group hitherto described.